2009
DOI: 10.1074/jbc.m808598200
|View full text |Cite
|
Sign up to set email alerts
|

The Death Effector Domain-containing DEDD Supports S6K1 Activity via Preventing Cdk1-dependent Inhibitory Phosphorylation

Abstract: ؊/؊ cells and tissues. Consequently, as in S6K1 ؊/؊ mice, the insulin mass within pancreatic islets was reduced in DEDD ؊/؊ mice, resulting in glucose intolerance. These findings suggest a novel cell sizing mechanism achieved by DEDD through the maintenance of S6K1 activity prior to cell division. Our results also suggest that DEDD may harbor important roles in glucose homeostasis and that its deficiency might be involved in the pathogenesis of type 2 diabetes mellitus.Cell size is closely related to specializ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Furthermore, DEDD associated with cyclin D3. This is similar to our previous observations that DEDD binds to various proteins such as cyclin B1, S6K1, and Akt (8)(9)(10)(11). As shown in Figure 6B, immunoprecipitation in HEK293T cells expressing both FLAG-tagged cyclin D3 and hemagglutinin-tagged (HA-tagged) DEDD showed that the two proteins coprecipitated, indicating that DEDD may facilitate a complex with cyclin D3.…”
Section: Decreased Akt Level In Dedd -/-Uteri and Increase In Polyplosupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, DEDD associated with cyclin D3. This is similar to our previous observations that DEDD binds to various proteins such as cyclin B1, S6K1, and Akt (8)(9)(10)(11). As shown in Figure 6B, immunoprecipitation in HEK293T cells expressing both FLAG-tagged cyclin D3 and hemagglutinin-tagged (HA-tagged) DEDD showed that the two proteins coprecipitated, indicating that DEDD may facilitate a complex with cyclin D3.…”
Section: Decreased Akt Level In Dedd -/-Uteri and Increase In Polyplosupporting
confidence: 90%
“…Consistently, depletion of DEDD results in a shortened mitotic duration, an overall decrease in the amount of cellular rRNA and protein, and decreased cell and body size (8,9). In addition to the function of DEDD as a cell-cycle regulator, we recently determined that DEDD associates with S6K1 (10) and Akt (11), major elements of the signaling cascade involving mitogen-related PI3K. Such associations support the roles of S6K1 activity and Akt protein stability, respectively, in contributing to the maintenance of glucose homeostasis in the body (10,11).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…DEDD is associated with CyclinB1/Cdk1 activity; specially decreasing the activity of Cdk1 allowing for sufficient ribosomal RNA/protein synthesis and cell growth prior to cell division by inhibiting Cdk1 regulated mitotic progression (39, 40). DEDD also interacts with Akt and S6K1 within the PI3K signaling cascade (41, 42). Dedd null mice are completely sterile, and the infertility is likely secondary to decidualization defects.…”
Section: Mechanisms Of Polyploidizationmentioning
confidence: 99%
“…DEDD plays an important role in CD95-mediated apoptosis in response to the activation of TNF-a through activating caspase-3 in cytoplasm or caspase-6 in nucleus as a scaffold protein (14). Recent studies found that DEDD can suppress the activity of Cdk1/ cyclin B1 complexes and keep S6K1 activity, suggesting that DEDD participates in the regulation of cell cycle and inhibits cell mitosis (15)(16)(17). Although other members of DED-containing proteins such as FADD have been implicated in a diverse array of diseases such as Huntington's disease, Type II diabetes, autoimmune disease, arthritis, and cancer (18), there is no direct evidence to show whether DEDD involves in the regulation of tumor development, growth, invasion, and metastasis.…”
Section: Introductionmentioning
confidence: 99%